2015
DOI: 10.5751/es-07927-200415
|View full text |Cite
|
Sign up to set email alerts
|

The Montérégie Connection: linking landscapes, biodiversity, and ecosystem services to improve decision making

Abstract: ABSTRACT. To maximize specific ecosystem services (ES) such as food production, people alter landscape structure, i.e., the types of ecosystems present, their relative proportions, and their spatial arrangement across landscapes. This can have significant, and sometimes unexpected, effects on biodiversity and ES. Communities need information about how land-use activities and changes to landscape structure are likely to affect biodiversity and ES, but current scientific understanding of these effects is incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…High stakeholder engagement in the development of the research project has been found to be key to PBSESR in three papers of this Special Feature in Ecology and Society that include many PECS-related projects , Mitchell et al 2015, Oteros-Rozas et al 2015. Although most of the projects assessed here reported interactions with stakeholders, different degrees of participation of stakeholders in project design were found.…”
Section: Discussionmentioning
confidence: 99%
“…High stakeholder engagement in the development of the research project has been found to be key to PBSESR in three papers of this Special Feature in Ecology and Society that include many PECS-related projects , Mitchell et al 2015, Oteros-Rozas et al 2015. Although most of the projects assessed here reported interactions with stakeholders, different degrees of participation of stakeholders in project design were found.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for landscape management, especially over large areas, as suggested by Qiu and Turner, as the structure of the landscape is something that land use planners can influence with reasonable precision. Different spatial patterns of land use and cover may benefit different services, and trade-offs between services can be mitigated or exacerbated by fragmentation at different scales 48, 49 . Landscape complexity, measured in terms of the proportion or diversity of natural habitat or its arrangement in the areas surrounding agriculture or both, enhances the pollination of crops 50 and pest control by natural predators 51 in a variety of cropping systems and regions 52 .…”
Section: Ecosystem Services and Sustainability Science: Key Steps Formentioning
confidence: 99%
“…However, many decisions require more information than can be gleaned from examining changes that have already occurred; policy-makers and other incentive setters wishing to promote the sustainable use of ESs have questions about where the most important places are to invest in conservation or restoration, what the impacts of allowing different types of development will be for different stakeholders, or how to most cost-effectively mitigate those impacts ( Table 1). In many cases, measuring ESs on the ground in specific places has led to empirical models that can inform decision-makers in those regions 48, 57 . For example, work by Fisher et al .…”
Section: Ecosystem Services and Sustainability Science: Key Steps Formentioning
confidence: 99%
“…As highlighted by several papers in this special feature (Hanspach et al 2014, Carpenter et al 2015, Mitchell et al 2015) participatory scenario planning is an increasingly popular tool in place-based environmental research for evaluating alternative futures of social-ecological systems. Oteros-Rozas et al (2015) review 23 cases of participatory scenario planning in a wide range of case-studies affiliated to PECS.…”
Section: Comparisons Across Cases and Social-ecological Systemsmentioning
confidence: 99%
“…They identify four types of scale mismatches in their landscape: two between production and benefit distribution, and two between ecosystem management and production. Mitchell et al (2015) investigate how current and historic landscape structure influences ecosystem service provision in the region. Their results suggest that landscape management decisions need to take into account landscape structure -such as connectivity and fragmentation -to effectively manage ecosystem services.…”
Section: This Special Featurementioning
confidence: 99%